'The referring court asks, in essence': Is reformulation of preliminary questions by the Court of Justice a decision writing fixture or a decision‐making approach?. Issue 4 (20th August 2019) - Šadl, Urška; Wallerman, Anna
Abstract: The Court of Justice can rephrase or otherwise depart from the questions referred to it by national courts under Article 267 of the Treaty of the Functioning of the European Union. It does so routinely: a practice known as reformulation. Legal literature often argues that reformulation is used to clarify national court questions and bring them within the scope of European Union law. The aim of the present article is to explore this claim systematically. To this end, it compiles a unique dataset consisting of the Orders for Reference, in which the referring courts embed the preliminary questions, and the judgments, in which the Court of Justice communicates the answers. The findings suggest that reformulation is a decision‐making approach rather than a fixture of decision writing. It's main function is to neutralize conflicts and Europeanise disputes. It underlines the Court's power to shape the preliminary ruling procedure and its outcomes.